STRATEGI KOMUNIKASI PENYIAR PROGRAMA 4 LPP RRI PADANG DALAM MEMPERTAHANKAN EKSISTENSINYA DI ERA GENERASI Z - Rahma Sari Rahayu; Fajri Ahmad (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2024)
This study aims to find out the communication strategy and constraints of RRI Padang program 4 broadcasters in the era of generation z. This research is a qualitative research with a descriptive approach, with data collection techniques in the form of observation, interviews and documentation. The results of this study provide findings covering four programs in program 4, as for the Communication Strategy of Broadcasters Program 4 LPP RRI Padang in Maintaining Its Existence in the Generation Z Era, namely: communication strategy of the broadcaster in the